2011
DOI: 10.1186/1471-2172-12-18
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 4 (TLR4) expression in human and murine pancreatic beta-cells affects cell viability and insulin homeostasis

Abstract: BackgroundToll-like receptor 4 (TLR4) is widely recognized as an essential element in the triggering of innate immunity, binding pathogen-associated molecules such as Lipopolysaccharide (LPS), and in initiating a cascade of pro-inflammatory events. Evidence for TLR4 expression in non-immune cells, including pancreatic β-cells, has been shown, but, the functional role of TLR4 in the physiology of human pancreatic β-cells is still to be clearly established. We investigated whether TLR4 is present in β-cells puri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
68
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 36 publications
5
68
2
1
Order By: Relevance
“…Both CXCR3 and TLR4 are expressed on beta cells [46,47] and subsets of NK cells [45,48], and gliadin is known to interact with both receptors [47,49]. Interestingly, a recent study has shown that amylase/trypsin inhibitor family members present in the ω-gliadin fraction are able to induce strong innate responses in human and murine macrophages, monocytes, and DCs via TLR4 [49], through a mechanism that could potentially induce IFN-γ secretion from NK cells [45].…”
Section: Discussionmentioning
confidence: 99%
“…Both CXCR3 and TLR4 are expressed on beta cells [46,47] and subsets of NK cells [45,48], and gliadin is known to interact with both receptors [47,49]. Interestingly, a recent study has shown that amylase/trypsin inhibitor family members present in the ω-gliadin fraction are able to induce strong innate responses in human and murine macrophages, monocytes, and DCs via TLR4 [49], through a mechanism that could potentially induce IFN-γ secretion from NK cells [45].…”
Section: Discussionmentioning
confidence: 99%
“…Although we have observed that HERV-W-Env is expressed in the pancreas by acinar cells surrounding β islets (Figure 1D), the concentration of HERV-W-Env to which the β cells are exposed in the pancreas in vivo can only be estimated to be locally elevated. Notably, a decrease in human β cell viability has already been described upon TLR4 activation after exposure to LPS (42).…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism of this inhibition requires further investigations, though it has already been described that HERV-W-Env exerts its pathogenic effects through an interaction with the TLR4 receptor (35,36). From a T1D perspective, this mechanism appears relevant, as TLR4 is expressed by β cells (42)(43)(44). Moreover, the inhibition of insulin secretion following TLR4 stimulation has already been observed in human, rat, and mouse pancreatic β cells by using lipopolysaccharide (LPS), the prototypical ligand of TLR4 (42,43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed there is an increase in the level of LPS in the circulation of those subjects and a low-grade endotoxemia, which are believed to play a role in the onset of the metabolic disorders (1). Pancreatic beta cells express significant levels of TLR4 which make them sensitive to the effect of LPS (10,14,40). Circulating LPS binding to TLR4 leads to activation of the nuclear factor kappa-light-chain-enhancer of activated B-cells (NF-B), p38 mitogen-activated protein kinases (p38 MAPK), activator protein 1 (AP-1), and interferon-inducible inflammatory gene expression (1,14).…”
Section: Discussionmentioning
confidence: 99%